Foreigners Everywhere : Biennale Arte 2024. - Margutti, Flavia Fossa; Pietragnoli, Maddalena; Pedrosa, Adriano; Carneiro, Amanda; Gotti, Sofia (s.l. : La Biennale di Venezia, 2024)
Beatriz, Cortez ; Olga De Amaral ; Hito, Steyerl (through the Disobedience Archive) ; Simone, Forti ; Samia, Halaby ; Lauren, Halsey ; Rindon, Johsnon ; Bouchra, Khalili ; Teresa, Margolles ; Ahmed, Morsi ; PuppiesPuppies (Jade Guanaro Kuriki) ; Zilia, Sánchez ; AnaSegovia ; Yinka, Shonibare ; Superflex ; Salman, Toor ; Kay, WalkingStick ; Etel, Adnan ; enz.
Deel 2: Participating Countries and Collateral Events ; Deel 1: Exhibition
La Biennale di Venezia, Venezia, 2024
boek